Residential college's smart restroom monitoring system - Azman, F. I.; Fazdli, M. S. F. M.; Saleh, N. L.; Noor, A. S. M.; Ali, A. M. (IEEE, 2023)
This paper presents the recent development in remote and smart monitoring of restroom cleanliness. This was achieved by incorporating Lora and Raspberry Pi together with physical sensors, which allow the transition from a predefined periodic cleaning to a usage-based approach. This allows measures to track the real-time use of restrooms and then derive longer-term patterns of usage.